2008
DOI: 10.1007/s11240-008-9337-5
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic potential in coconut (Cocos nucifera L.)

Abstract: Conditions for induction of androgenesis in coconut cv. Sri Lanka Tall were studied. Anthers collected from inflorescences at four maturity stages were given heat (38°C) or cold (4°C) pretreatments for 1, 3, 6 and 14 days, either prior to or post inoculation. Three different basal media and different anther densities were also tested. Androgenesis was observed only in anthers collected from inflorescences 3 weeks before splitting (WBS) and after a heat pretreatment at 38°C for 6 days. Modified Eeuwens Y 3 liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 37 publications
5
37
0
1
Order By: Relevance
“…2b, 2c, 2d). This result resembled to embryo and callus formation of pollen grain culture of coconut (Perera et al 2008). Formation of proembryo structures could happen without suspensor (Fig.…”
Section: Calli Cultured In Liquid Mediumsupporting
confidence: 59%
“…2b, 2c, 2d). This result resembled to embryo and callus formation of pollen grain culture of coconut (Perera et al 2008). Formation of proembryo structures could happen without suspensor (Fig.…”
Section: Calli Cultured In Liquid Mediumsupporting
confidence: 59%
“…The activated charcoal (AC) in the maturation medium can adsorb inhibitory substances such as phenolic compounds, ethylene or auxin residues that could prevent the development of somatic embryos (Pereira et al 2008, Aboshama 2011. In a study investigating the maturation of somatic embryos of different varieties of grape, López-Pérez et al (2005) found that the use of a medium supplemented with AC (2.5 g L -1 ) produced a significantly higher maturation rate (99.5%) than the medium without AC (5.8%).…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%
“…In those early studies, neither ploidy level determination nor plantlet regeneration was reported. However, in a more recent series of studies it has been reported that somatic embryo structures, with root and shoot apices, have been produced through anther culture (Perera et al 2007a(Perera et al , 2008a, and finally homozygotic plants (Perera et al 2008b). The basic procedures now used employ a culture medium developed by Karunaratne and Periyapperuma (1989) and supplemented with a high concentration of sucrose (9 %) (Perera et al 2008a(Perera et al , 2009c.…”
Section: Homozygote Production Via Anther Culturementioning
confidence: 99%